Planes, trains & automobiles: The future of transport after Covid-19 - Richard Wellings (Institute of Economic Affairs (IEA), 2022)
Transport played a central role during the pandemic, with aviation facilitating the rapid global spread of Covid-19. The sector was targeted by governments that imposed draconian restrictions on mobility in an attempt to reduce transmission, but at the same time supported the aviation and rail industries with large bailouts. The pandemic and associated lockdown policies led to a steep change in the uptake of alternatives to travel. Improvements in technology have made it easier to work from home, shop online and hold virtual meetings. These developments have the potential to deliver significant cost savings and productivity gains by reducing transport costs and the need for retail and office spaces. The impact on transport markets could be dramatic. A significant fall in demand or even a decline in rates of growth mean expected revenues will not materialise. The economic case for many infrastructure projects is likely to be severely weakened. The shift to alternatives to travel is likely to vary significantly by sector, which will affect the impact on different transport modes. Working from home is only feasible for certain jobs, and virtual meetings are only possible for certain businesses. The rail sector is particularly vulnerable to upheaval. Many rail users - concentrated in high-income groups and white-collar jobs - have been able to shift to working from home and virtual meetings relatively easily. The sector is also heavily dependent on taxpayer support at a time when there are severe constraints on government spending. The level of rail subsidies is clearly out of any reasonable alignment with ridership and passenger income. Costs could be contained by reducing fragmentation in the industry and re-privatising the sector with a more efficient structure. Car travel may be an unexpected beneficiary of the Covid-19 crisis, especially in some regions of the country. Disease-driven restrictions on other modes of transport make car travel seem relatively more convenient, while increased working from home may speed up journeys by reducing peak-time congestion. Improvements in communications infrastructure, spurred in part by the pandemic, could facilitate more rapid adoption of autonomous vehicles. In contrast, Covid-19 is likely to have a negative long-term impact on aviation. The threat of future pandemics could encourage policymakers to adopt a more hostile stance towards air travel and long-distance connectivity more generally.
Keywords: 330; Coronavirus; Impact assessment; Air transport; Airline; Rail transport; Rail company; Road transport; United Kingdom; Coronavirus; Wirkungsanalyse; Luftverkehr; Fluggesellschaft; Schienenverkehr; Eisenbahnunternehmen; Straßenverkehr; Großbritannien